PENTINGNYA BUDAYA ORGANISASI TERHADAP KINERJA TENAGA KEPENDIDIKAN: TINJAUAN STUDI LITERATUR - Ahmad Nopriansyah; Oktariana; Masbirorotni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Education in the modern era requires a dynamic and responsive system to ensure the provision of good and quality education. In an effort to improve the quality of education, internal organizational factors, especially organizational culture, play an important role in forming a conducive, positive and motivating work environment for education staff. Organizational culture includes the shared values, norms, and beliefs held by members of an organization. As an integral component in organizational life, organizational culture has the potential to influence the behavior, motivation and performance of individuals who work in it. In particular, education personnel, who play a vital role in delivering and managing education, can be influenced by organizational culture that supports or even hinders the achievement of educational goals. Emita et al. (2021) explains that organizational culture variables have an important role and significantly influence employee performance. The writing method used is literature study, where this literature study research method involves analysis and synthesis of existing literature or writings to produce an in-depth understanding of the research topic or problem. The research details the importance of organizational culture on the performance of educational staff through understanding the concept of organizational culture, its relationship with motivation and job satisfaction, as well as the factors that influence the formation of organizational culture. These findings provide in-depth insight for educational leaders and human resource management practitioners to design policies and strategies that strengthen organizational culture to improve the performance and satisfaction of educational staff in educational institutions